Mindfulness and Other Psycho-Social Resources Protective Against Mental Illness and Suicidality Among Gay Men - Wang, Jen; Häusermann, Michael; Ambresin, Anne-Emmanuelle (Frontiers in Psychiatry, 2018)
Background: There is considerable evidence of health disparities among gay men characterized by higher levels of stress and distress. Psycho-social resources have been linked to numerous positive health outcomes and shown to act as buffers in the stress-distress pathway. Methods: With data from the 3rd Geneva Gay Men’s Health Survey carried out in 2011 using time-space sampling (n=428), a relatively elaborate profile of 14 psycho-social resources—including mindfulness—is presented. Using their original scores, latent class analysis created an index variable dividing the respondents into meaningful groups. Psycho-social resources—the index variable as well as each resource individually—were then compared to two recent outcomes—i.e., serious mental illness in the past 4 weeks and short-term disability in the past 2 weeks—using a series of logistic regression models, controlling for all other psycho-social resources and socio-demographic confounders. To assess their potential role as buffers, a similar series of logistic regression models were erected using victimization and three outcomes—i.e., major depression, suicidal ideation, and suicide attempt—in the past 12 months. Results: According to the latent class analyses, 5.1% of this sample had a low level of psycho-social resources (i.e., one standard deviation (SD) below the group means), 2) 25.2% a medium-low level, 3) 47.4% a medium level (i.e., at the group means), and 4) 22.2% a high level of psycho-social resources (i.e., one SD above the group means). Psycho-social resources were strongly protective against recent mental morbidity and buffered against the impact of victimization on major depression and suicidality in the past 12 months, reducing the adjusted odds ratios below statistical significance. The explained variance and the individual psycho-social resources which remained independent in the models differed for each outcome. Conclusions: There may be disparities in several psycho-social resources among gay men, and as strong compensatory and protective factors, they may explain in part the well-established disparities in stress and distress in this population. While multiple psycho-social resources should be promoted in this population, gay men under 25 years should receive particular attention as all three disparities are most pronounced in this age group.